Paediatric infected non-union of an open femoral diaphyseal fracture: the role of temporary locking plate and bone graft substitute - Kow, Ren Yi; Ab Rahman, Zamri; Chooi, Leng Low; Mor Japar Khan, Ed Simor Khan; Jaya Kumar, Ruben (Crimson Publishers, 2018)
Chronic osteomyelitis is a complication of open fractures in children especially in rural areas. It is difficult to treat, and it may lead to infected non-union. We present a case of an open fracture Gustillo-Anderson grade IIIa complicated with chronic osteomyelitis. He presented with non-union six months post-trauma after the initial surgical debridement and bone resection. He was subsequently treated successfully with a temporary 3.5mm locking plate and synthetic bone graft. A temporary locking plate can stabilize the fracture site and provide additional advantage in terms of wound management and earlier joint motion in comparison with external fixation and cast.